(3GdfhGOQ aj GddZIs - (3SYjO Hf ChS Hf KGHJ Hf RjO Hf bjS GdCfUGQj, CHh RjO,J (B215 (3g` s ((3YHO Gddg eMeO Hf GdecQe Hf CHj GdMSf Hf CMeO GdCfUGQi GdMeOMi s)
(3ChdgG (B:s
(3CNHQfG CHh ESMb EHQGgje Hf eMeO Hf CMeO Hf HSGe HGH TYQ bGd CHh RjO CfTOfi GdeaVd dVeQg Hf VeQg GdgfSJdi hgh LGgdi HcQJ fdhec HYO hgf ai GdYQi jSHd Ydjc edGeJi hYJGHi s
(3BNQgG (B:s
(3hjbGd CfS hjLeY BfGS eSehY bGd CHh MGJe hdYdc CfS hCfGS Je cJGH GdhGOQ heG jVGa Edjg ef cJGH eSGFdg dCHi RjO s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B92 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B220s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GddZIs